The restorative effects of green spaces with animals on stress - Zahra, Arianne Muthia; Masrura, Aidal; Bohari, Rina Hazwani; Imtiaz, Shamim; Mohd Mahudin, Nor Diana (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)
Past research on restorativeness has concentrated mainly on the potential of vegetation, scenic environments, parks, and open spaces rather than on natural environments with animals. At present, the restorative effects of green spaces with animals on people's general well-being and psychological stress remain unclear. This study argues that green spaces with animals, such as zoo, are also likely to have a restorative influence on human psychological stress and overall well-being. A between-group experiment was conducted, in which 80 randomly selected visitors of the Malaysian National Zoo were asked to answer two scales, i.e. the adapted Kessler Psychological Distress Scale (K10) and the Perceived Restorativeness Scale (PRS). Results showed that, contrary to the hypothesis, there is no significant relationship between stress and restorative effects of the green spaces with animals. However, statistical data indicate that most participants reported experiencing higher levels of restorative effects and lower levels of stress after they visited the zoo. These findings are generally supportive of cognitive model of attention restoration and point to the importance of enhancing the restorative qualities of the zoo’s environment and rebuilding the unity between man and nature.